Sterols from Jatropha tanjorensis leaves exhibit anti-inflammatory potential: in vitro and in silico studies - Damilola Alex Omoboyowa (SpringerOpen, 2021)
Abstract Background Inflammation has continued to raise global challenges and Jatropha tanrogenesis (JT) is used traditionally for its management. In this study, the in silico and in vitro anti-inflammatory potential of bioactive sterols were investigated. The active compounds of ethanol extract of JT leaves were identified using Gas chromatography-mass spectrometry (GC.MS) followed by molecular docking against COX-1 and COX-2 using maestro Schrödinger and pharmacokinetic profile prediction using webserver tools. The in vitro anti-inflammatory and anti-oxidantive potentials were investigated using standard protocols. Results GC–MS analysis of ethanol extract of JT leaves revealed the presence of eight (8) compounds, the molecular docking analysis of these compounds demonstrated varying degrees of binding affinities against the target proteins. The extract exhibit concentration dependent anti-oxidant activity with IC50 of 106.383 and 6.00 Fe2+E/g for DPPH and FRAP respectively. The extract showed significant (P < 0.05) reduction in percentage inhibition of hemolysis at 200 µg/ml while non-significant (P > 0.05) increase was observed at 600 and 1000 µg/ml compared to 200 µg/ml of diclofenac sodium. At lower concentration of 25 and 50 µg/ml, percentage inhibition of albumin denaturation was significantly (P < 0.05) higher compared to 200 µg/ml of diclofenac sodium. Drug likeness prediction and ADME/toxicity screening showed that the bioactive compounds possess no side effects. Conclusion The results obtained in this study suggested that, JT leaves possess anti-inflammatory activity and could be used as a source of new drug.